Effect of Using Combined Oral Contraceptive on Thyroid Hormones and Lipid Profile in Female - S. Oubeid, Wasan; H. Salih, Hiba; H. Hadry, Dakhel; A. Jasim, Nawar (Tikrit Journal of Pharmaceutical Sciences, 2023)
This study was performed to know the effect of contraceptive pill on the thyroidhormone triiodothyronine, thyroxin, and thyroid stimulating hormone, and lipidprofile, (total cholesterol, triglyceride, and, high density lipoprotein). Blood sampleswere collected from 60 women's at the midcycle which divided to two groups, group(A) consist of 30 women taking combined oral contraceptive more than one year. andgroup (B) which consists 30 women never take oral contraceptive and considered ascontrol group. The age of these women varies from 20 to 35 years. The results of thecurrent study showed that the levels of triiodothyronin and thyroxin weresignificantly higher among women taking combined contraceptive compared tocontrol group, while the TSH level was significantly lower in group A although itwas in the normal range, comparative with control group. The level of triglycerideand total cholesterol were significantly higher in women of group (A) comparativewith control group (B), and the HDL level was significantly lower among combinedcontraceptive users compared to control group.